Flow Experience: A Phenomenological Study on Casual Gamer - Mario Rizky Yuwono; Jony Eko Yulianto; Nono Hery Yoenanto (Universitas Ciputra Surabaya, 2024)
Articles about flow experience in game have been done many times to hardcore gamers. However, the definite description of flow experience in gaming have not been found yet. There have been many flow experience assessment methods in gaming but none have been acknowledged as a good one. in which create some difficulties to measure flow experience in gaming. This article aimed to understand the construct of flow experience in casual gamers. Three casual gamers of age 19-24 years old that resides at Surabaya, Indonesia were interviewed in a semi-structured interview. Result revealed the aspect of ‘time’, which have been named ‘time availability’, is the unique factor that leads casual gamers to experiencing flow. We concluded that casual gamers experiencing similar flow experience as hardcore gamers. That being said factors that lead gamer to flow experience differentiate the casual and the hardcore.